The scientific and historical position, jurisprudence and personality of imam sadiq from the sunnis point of view (Journal of history, 2022)
Imam Sadiq is one of the scientific, jurisprudential, and moral pioneers of our time and an outstanding personality of the Islamic world and humanity. He established a large scientific center in Masjid al-Nabi located in Madinah Munuwrah, which had the status of the first university in the world, and educated up to four thousand students in various branches of religious and intellectual sciences of the time, a valuable contribution to the flourishing of Islamic civilization, the production of sciences in the fields of different and scientific guidance of people. He is a personality who does not fit in the form of a single religion, religion or sect, but the whole of humanity is indebted to the efforts of intellectual sciences and the publication of religious sciences by that honorable man. Famous scientists and thinkers such as Imam Azam Abu Hanifa, the leader of the Hanafi religion, Imam Malik Ibn Anas, the leader of the Maliki religion in religious sciences, and Jabir Ibn Hayyan and others in experimental and intellectual sciences were his students. Many scholars of different sects, both Muslim and non-Muslim, have spoken about the knowledge, knowledge, asceticism, chivalry, morals, behavior and characteristics of that noble person and have described his eminence as the universe leader. The scientific, jurisprudential and personal status of Imam Sadiq is prominent in the eyes of all Muslims, and he does not belong to a particular religion, but belongs to all Muslims and humanity. Key words: Imam Sadiq, Ahl al-Sunnah, scientific position, jurisprudential position, personality.